Upaya Meningkatkan Kemampuan Passing Atas Pada Permainan Bola Voli Dengan Menggunakan Model Pembelajaran Teams Games Tournament Pada Siswa Kelas VI SDN 2 Cipakem - Agus, Agus (Journal of Physical Education and Sport Science, 2024)
Improving Upper Passing Ability in Volleyball Game Using Teams Games Tournament Learning Model for Class VI SDN 2 Cipakem Students.The purpose of this study is to improve the learning outcomes of passing over in volleyball games through the Teams Games Tournament learning model in class VI SDN 2 Cipakem. This type of research is classroom action research. The subjects in this study were sixth grade students consisting of 16 students with 7 male students and 9 female students. Based on the results of the Upper Passing assessment test in the Volleyball Game through the Teams Games Tournament Learning Model for Class VI SDN 2 Cipakem in the first cycle of 16 students, the scores of students who have reached the KKM are 5 people with a percentage of 31%, while 11 students have not reached the KKM score. KKM with a percentage of 69%. So this research was continued with the implementation of the second cycle and the results increased by the number of 16 students, then the score of students who had reached the KKM were 12 people with a percentage of 75%, while 4 students had not reached the KKM score with a percentage of 25%.